2022
DOI: 10.34067/kid.0005442022
|View full text |Cite
|
Sign up to set email alerts
|

Heme Proteins and Kidney Injury: Beyond Rhabdomyolysis

Abstract: Heme proteins, the stuff of life, represent an ingenious cellular strategy that capitalizes on the biochemical versatility of heme, and yet is one that avoids the inherent risks to cellular vitality posed by unfettered and promiscuously reactive heme. Heme proteins, however, may be a double-edged sword as they can damage the kidney in certain settings. While such injury is often viewed mainly within the context of rhabdomyolysis and the nephrotoxicity of myoglobin, an increasing literature now attests to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 119 publications
0
21
0
1
Order By: Relevance
“…19 In addition, prior studies support that free heme can lead to tubular injury by various mechanisms, including proximal tubular uptake using the megalin/ cubilin complex, altered cellular cytoskeletal structure because of pro-oxidant properties, impaired cytosolic enzymes, and proinflammatory properties based on in vivo studies. 9,10,20 One intriguing question is whether an underlying genetic polymorphism, such as genes associated with GBM composition and structure, may explain the presence of hematuria in some patients and confer a higher risk of disease progression. In a study of over 3000 patients with mixed etiologies of CKD, including glomerular disease, 66 monogenic disorders were detected in 307 patients, of which 30% were collagen IV gene variants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 In addition, prior studies support that free heme can lead to tubular injury by various mechanisms, including proximal tubular uptake using the megalin/ cubilin complex, altered cellular cytoskeletal structure because of pro-oxidant properties, impaired cytosolic enzymes, and proinflammatory properties based on in vivo studies. 9,10,20 One intriguing question is whether an underlying genetic polymorphism, such as genes associated with GBM composition and structure, may explain the presence of hematuria in some patients and confer a higher risk of disease progression. In a study of over 3000 patients with mixed etiologies of CKD, including glomerular disease, 66 monogenic disorders were detected in 307 patients, of which 30% were collagen IV gene variants.…”
Section: Discussionmentioning
confidence: 99%
“…11 Fewer studies in adults reported the prevalence of hematuria by disease. In 410 adult patients in India, hematuria was present in 20 minimal change disease, and 25% (23/92) with membranous nephropathy. 12 Among 95 adults with minimal change disease, 28.9% had hematuria at presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] Moreover, in virtually all forms of AKI, kidney content of heme may increase because of destabilization of heme proteins (especially p450 cytochromes) in the injured kidney 7,9,10 ; this leads to the release of heme, the latter being a nephrotoxic and proinflammatory metabolite. 7 Heme proteins may thus contribute to diverse types of AKI. 7,8 HP-AKI, induced by the intramuscular injection of hypertonic glycerol (which causes myolysis and hemolysis), has long and widely been studied by our and other laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…The release of excessive amounts of heme from intracellular proteins is inherently dangerous 1 . There are numerous conditions associated with the release of heme, or free heme, which can lead to oxidative and inflammatory harm [2][3] .…”
Section: Introductionmentioning
confidence: 99%